A study on the effectiveness of using drama techniques in teaching English: Trainee teachers and students' perspectives / Nur Anissa Abd Azis - Abd Azis, Nur Anissa (Faculty of Education, 2014)
This study investigated secondary school students and trainee teachers' perceptions towards the effectiveness of using drama techniques in teaching English. It also examined students' feedback on the benefit of drama-based activities to their motivation to learn, selfesteem and anxiety. The subjects of this study involved 50 Form Two students from a secondary school situated in the sub-urban area of Klang Valley, specifically Subang and also two trainee teachers who have taught at schools in that area. The study employed two method of collecting data which were questionnaire and interviews. The findings in this study indicate that majority of the students feel that drama techniques is effective as it helps improve their motivation to learn, increase their level of self-confidence and reduce their language anxiety in the teaching and learning process. The students' perception was supported by trainee teachers' point of view that really favors the use of drama techniques and had given their testimony on the effectiveness of the using drama-based activities in the classroom. The most significant finding reveals that both students and trainee teachers support the notion of the effectiveness of applying drama techniques in teaching English as it benefits students not only in terms of academic but it also contribute to students' affective development.